Heart and longevity — clinical and instrumental features - L. I. Malinova; T. P. Denisova; S. S. Shuvalov (Кардиоваскулярная терапия и профилактика)
Aim. Due to the leading position of cardiovascular disease in the mortality and morbidity structure, it is important to investigate specific cardiovascular system features in the long-living elderly. Material and methods. In total, 200 long-living Saratov citizens were examined, 161 as out-patients and 39 as inpatients. Results. The clinical parameters of senile heart were identified, as well as the main characteristics of cardiac rhythm and conductive system in long-living individuals. Specific features of the heart failure clinical course were described. Conclusion. InSaratov citizens, the main medical and social predictors of longevity included female gender, regular physical activity, moderation-focussed lifestyle, absence of alcohol abuse or smoking, and positive personality